Asam HidroksiAsam Hidroksisinamat dari Drynaria sparsisora ​​sebagai Agen Anti-Vibrio: Bukti Terintegrasi In Vitro dan In Silicosinamat dari Drynaria sparsisora sebagai Agen Anti-Vibrio: Bukti Terpadu Secara In Vitro dan In Silico - Hesti Marliza; Fitra Perdana; Yuli Haryani; Hilwan Yuda Teruna; Rudi Hendra (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Drynaria sparsisora is a fern species long utilized in ethnomedicine and recognized as a source of phenolic compounds. This study aims to isolate antibacterial ingredients from D. sparsisora, evaluate their efficacy against Vibrio species, and investigate potential molecular interactions by in silico docking analysis. Dried plant material was extracted with methanol and separated by liquid–liquid partitioning followed by chromatographic purification. Two main compounds were identified and structurally characterized using UV–Vis, FTIR, and ¹H/¹³C NMR spectroscopy. Spectroscopic measurements established the identification of the substances as ferulic acid (1) and caffeic acid (2). In vitro antibacterial activity was investigated against Vibrio alginolyticus, Vibrio parahaemolyticus, and Vibrio cholerae using a broth microdilution method to determine minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Both isolated compounds displayed MIC values of 20 µg/mL and MBC values of 40 µg/mL against all tested strains, leading to an MBC/MIC ratio of 2, confirming bactericidal activity. Although chloramphenicol revealed higher efficacy (MIC 12.5 µg/mL), the separated phenylpropanoids showed consistent and repeatable suppression across all Vibrio species tested. To give mechanistic insight, molecular docking simulations were performed against three bacterial protein targets (PDB IDs: 2ZDQ, 1HNJ, and 3IL7). Both ferulic acid and caffeic acid displayed favorable binding energies and persistent interaction patterns inside the active regions of these proteins, involving hydrogen bonding and hydrophobic interactions. In selected models, docking affinities neared those of chloramphenicol, confirming the likelihood of target engagement. The multi-target binding behavior found suggests possible interference with important bacterial functions, including cell wall function, protein synthesis, and fatty acid production. Overall, the data reveal that D. sparsisora contains hydroxycinnamic acids with considerable bactericidal activity against Vibrio spp., backed by computational evidence of protein interaction. Further investigations are necessary to validate molecular targets and clarify antibacterial processes.